Chaotropic salts interacting with soft matter: Beyond the lyotropic series. (June 2016) - Leontidis, Epameinondas
Abstract: The effects of the chaotropic ions of the Hofmeister series on many systems and phenomena are typically quite pronounced. What happens, however, when one uses chaotropic ions beyond SCN −, ClO4 −, or guanidinium, which are the usual limiting ions of the lyotropic series considered in most investigations? This review focuses on the extensive but scattered literature that discusses how larger hydrophobic ions and hydrotropic ions interact with soft matter. There are many similarities between hydrophobic and hydrotropic ions; they differ in the fact that the hydrotropes are intrinsically asymmetric with respect to aqueous solvation. Strong specific effects of these ions with a common denominator are found in diverse systems: Hydrophobic ions "stick" to hydrophobic surfaces, or intercalate within soft matter interfaces, becoming a basic component of the structure and often inducing disruption or phase change. In other situations, hydrophobic ions act indirectly by failing to provide adequate screening of electrostatic interactions because of their large size. The hydrophobic and hydrotropic ions discussed here constitute the link between the lyotropic series and the surfactant domain. It is pointed out that, despite the size and breadth of the literature, there is still much work to be done to clarify how these ions interact with soft matter. Many important applications can result from the control of soft matter structure that can be achieved with these ions. Graphical abstract: Highlights: Effects of hydrophobic and hydrotropic ions on soft matter are examined. Hydrophobic ions induce protein denaturation and DNA melting. Further experiments to elucidate hydrophobic ion action are suggested. Hydrotropes act as co-surfactants or as quasi-surfactants in soft matter systems. The lyotropic anion line is extended in the region of extreme chaotropy.